SITUS SENI CADAS SEBAGAI ASET BUDAYA DAN PEMBANGUNAN PARIWISATA (Studi pengembangan situs seni cadas di kawasan Teluk Bicari dan Selat Maimai, Kabupaten Kaimana, Papua Barat) - Djami, Erlin Novita Idje (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
Rock art sites in the area of the cultural assets worth Kaimana high for the sake of history, science and culture, so it’s worth it if it is developed and utilized. It is also considering the condition of the site is supported with the surrounding natural beauty of the ocean and coral islands, as well as the charm, the expanse of the forest in karst area and village-village population is about. To optimize the potential of art rock then needs to be done the study development on rock art sites in the region, as a form of Kaimana policy implementation in the management of cultural heritage and its environment so that it can have an impact on the increase of living adequate for the present society (especially the local community) in the field of persons coming. Results of the survey has been conducted showing that in the process of development of tourism in the region need to involve local communities Kaimana as key stakeholders, both in the planning and implementation of policies in a bottom up, determined policy along community, as well as patisipasi actively involved in community development programs and support the development of business and economics which is the economic base of society, as well as the need to be supported by regulation as runway departure formally related protection, preservation and utilization of cultural objects.